Sampling in archaeology - Orton, Clive (Cambridge manuals in archaeology, 2000)
"The first overview of sampling for archaeologists for over twenty years, this manual offers a comprehensive account of the applications of statistical sampling theory which are essential to modern archaeological practice at a range of scales, from the regional to the microscopic. Bringing archaeologists up to date with an aspect of their work which is often misunderstood, it includes a discussion of the relevance of sampling theory to archaeological interpretation, and considers its fundamental place in fieldwork and post-excavation study. It demonstrates the vast range of techniques that are available, only some of which are widely used by archaeologists. A section on statistical theory also reviews the latest developments in the field, and the formal mathematics is available in an appendix, cross-referenced with the main text."--BOOK JACKET.